PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PEMELIHARAAN DAN PERBAIKAN MESIN (SIMPAN) PADA PT. G+D INDONESIA - D. Hedin Purnama; Azihi Mahfaza; Purwanto (Institut Sains dan Teknologi Al-Kamal, 2022)
G+D Indonesia is a company engaged in the sale and maintenance of banking machines and has been operating in Indonesia since 2008, and has many partners in Indonesia. Today the existing of maintenance system uses manually. The number of partners who must be served after the machine purchase (after sale) needs to be managed properly so that machine maintenance and repairs are scheduled properly. Therefore the maintenance Information System is very much needed to help company in managing and maintenance machine so that service to customers is better.This research aims to 1) build maintenance Information System, 2)provides sevices to customers easily and quickly. This maintenance Information System uses waterfall methode and process design uses UML as a framework to describe the processes that occur, and implemented uses codeigniter as a back end framework using PHP programming language, bootstrap as a front end framework and uses SQLExpress as the database, and Apache as the web server.